Optimalisasi Usaha Mikro Produksi Tempe Terhadap Kesejahteraan Ekonomi di Desa Sei Mencirim - Annisa ilmi faried; Saimara Sebayang; Rahmad Sembiring (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
In the current era of competition, there are various developments in the industrial sector both on a small and medium scale. Sustainable development becomes the goal in improving the creative economy of society in meeting the needs of life. One of them is in small business processing tempeh that still uses traditional equipment as well as family hereditary businesses that are inherited from generation to generation. Tempeh will still continue to be in demand by the public, although tempeh sellers in traditional markets continue to be dreamed up by modern retail. Not to mention many tempeh entrepreneurs who can not add value to the product by processing tempeh into other foods because constrained do not have the expertise to innovate and marketing. Determinants of this research are labor, capital, natural resources, technology as well as social factors towards production and prosperity. The number of samples in this study was 239 KK. The data is collected through the questionnaire method, then done by structural equation modelling (SEM) method. The results on the hypothesis of labor, capital, natural resources, technology and social factors have a significant effect on production. Then natural resource variables, social factors and production have a significant effect on well-being while labor, capital and technology variables have no significant effect on well-being